MENDETEKSI ORISINALITAS CITRA DIGITAL DENGAN MENERAPKAN METODE ADLER-32 - Jelita Lahagu (KOMIK (Konferensi Nasional Teknologi Informasi dan Komputer), 2019)
The development of digital images is now very rapid, where the processing of image data, documents on digital images make images easily created or manipulated easily, even without leaving a visual imprint for users to manipulate an image. The ease in making and changing an image can damage the credibility of the originality / authenticity of the image in various aspects.Image is a combination of points, lines, shapes and colors to create an imitation of an object. Based on this, the pixel changes the original image so that it does not indicate the original image or the image has been manipulated. Thus the detection of the image can be known the authenticity of an image using the Adler-32 Algorithm.  Small changes of pixels do not make the image content detected by the human eye. This is explained in pixels like the long width in the image. The basis of this research is to detect the originality or authenticity of a digital image. Keywords : Image, Originality, Manipulation, Adler-32